2020
DOI: 10.1109/access.2020.3021650
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Diffuse Coding Metasurface of Independent Polarization for RCS Reduction

Abstract: In this paper, a multiple diffuse coding metasurface (MDCM) of independent polarization is designed to control the propagation direction of diffuse reflections under different polarizations and to improve the monostatic and bistatic RCS (radar cross section) reduction effect. First, a method for controlling the distribution range and propagation direction of the diffuse field is studied, and the diffuse field distribution of the random phase metasurface is optimized by a genetic algorithm to improve the unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Table 1 lists the comparison of the coding metasurface with previous works presented in Ref. [35][36][37][38][39][40][41], it is indicated that the coding metasurface can achieve much wider band RCS reduction, so it has great potential in radar stealth technology application.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Table 1 lists the comparison of the coding metasurface with previous works presented in Ref. [35][36][37][38][39][40][41], it is indicated that the coding metasurface can achieve much wider band RCS reduction, so it has great potential in radar stealth technology application.…”
Section: Discussionmentioning
confidence: 95%
“…It can work as a reflective phased array antenna, its far-field scattering pattern can be controlled by the predesigned coding sequence, so it can achieve Radar Cross Section (RCS) reduction by optimizing the coding sequence. In recent years, to realize wideband RCS reduction, a number of different coding metasurfaces have been proposed [35][36][37][38][39][40][41] .…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, a concept of coding metasurface was firstly proposed by Cui et al, [16] which consist of several different types of coding elements with much different reflection phases, it can work as a reflective phased array antenna, and the array pattern can be represented by a coding sequence, so its far-field scattering pattern can be controlled by the predesigned coding sequence, and according to a proper coding sequence, the anticipated RCS reduction can be realized due to phase cancellation. In recent years, to realize wideband RCS reduction, a number of different coding metasurfaces have been proposed [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion of backscattered electromagnetic (EM) waves and radar cross section (RCS) reduction of objects using metasurface have received a lot of attention among researchers in recent years [1]- [8]. Metasurfaces are the 2D version or counterparts of the 3D metamaterials which are usually composed of an array of sub-wavelength dimensions metallic or dielectric resonators [13]- [14].…”
Section: Introductionmentioning
confidence: 99%